Prevalence of suicidal ideation and its associated factors among the geriatric population in Vyas Municipality, Tanahun District, Nepal: a cross-sectional study - Durga Shrestha; Hari Prasad Kaphle (BMC Geriatrics)
Abstract Background Suicidal ideation among the geriatric population is a pressing concern, particularly in regions such as Nepal where mental health resources are limited. This study aimed to determine the prevalence of suicidal ideation and its associated factors among the geriatric population in Vyas Municipality, Nepal. Methods A cross-sectional study was conducted among individuals aged 60 years and above in Vyas Municipality, Nepal. A total of 311 participants were selected using multistage sampling. The data were collected through face-to-face interviews using a structured interview schedule. Multivariate logistic regression analysis was performed to identify independent variables associated with suicidal ideation. Results The overall prevalence of suicidal ideation within the last twelve months among the geriatric population was 6.4% (n = 20). After adjustment for covariates in multivariate logistic regression analysis, living in a nuclear family (OR: 3.033, C.I. 95%:1.007–9.136), and experiencing depressive symptoms [(Mild depression:- OR: 5.358, C.I. 95%:1.548–18.539), (Moderate depression:- OR: 15.739, C.I. 95%:2.536–97.687), and (Severe depression:- OR: 17.423, C.I. 95%:2.218-136.878)] were found to be significant influencing factors for suicidal ideation. Conclusion This study emphasizes the need to enhance mental health services and strengthen family and community support systems to address suicidal ideation among older adults in Nepal. Further research is required to identify additional determinants and evaluate interventions to mitigate this risk.